The Impact of EU’s Black Campaign on the Export Volume of Indonesian CPO to EU in 2019-2023 - Simatupang, Harold Lembang; Moenardy, Dwi Fauziansyah (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2025)
This study examine the consequences of the EU's black campaign on the volume of Indonesia's crude palm oil (CPO) exports to the EU from 2019 to 2023. Using qualitative methods, it analyzes primary data from informants and secondary data from relevant documents. The findings reveal that the Black Campaign and the policies implemented by the EU have significantly contributed to a decline in Indonesia's CPO export volume towards the EU, caused by the damaging portrayal of Environmental issues that are not accurate and the hindrance of export growth caused by protective policies such as RED II. This research contributes to theories in international trade and offers insight for strengthening standardization and certification on of CPO in Indonesia. The implications of this study are critical for understanding the intersection of Environmental concerns and trade policies, for fairer practices in international trade that consider the realities faced by producing countries like Indonesia.